RETHINKING CHIKKU KOLAM FOR MODERN ADAPTATION. A STUDY ON THREE DIMENSIONAL INTERPRETATIONS OF THE TRADITIONAL ART OF CHIKKU KOLAM - Kondury, Hima Bindu (International Journal of Research -GRANTHAALAYAH, 2025)
Chikku Kolam is a traditional floor art practiced even today in states of Tamil Nadu, Andhra Pradesh and parts of Karnataka and Kerala. Chikku kolam emerges as a more complex form of simple rangoli patterns that are seen in different parts of the Indian subcontinent. Known with different names such as Alpana in West Bengal, Aipan in Bihar, Mandana in Rajasthan etc these patterns mostly follow simple geometric principles of symmetry, radial expansion and mirroring while highlighting a central focal point. The designs seen in these rangoli are mostly floral or nature inspired designs. In Chikku Kolam of the South Indian states, the designs become more complex making use of geometry and mathematics such as grids, algorithms and fractal expansions. The patterns also take a complex form where a single line is looped around a predetermined dotted grid in a predetermined path. The patterns are so complex that once it is made it becomes impossible to pinpoint the start and end of the loop giving rise to a pattern described as the endless knot. Yet the patterns are limitless and with their own symbolism and meaning and have various designs for different occasions and rituals. This age old art form though has been widely studied by enthusiastic mathematicians and computer program developers for understanding algorithms, computation and mathematical permutations and combinations, these gridded and looped patterns have immense potential to be explored in a 3 dimensional form hence creating an interesting scope of study. By using modern 3d software and programs these traditional patterns can be extruded into 3d forms creating exciting forms which could be applied in various disciplines such as architecture, installation art, product design etc. This research paper aims to look at these chikku kolam patterns with a modern appreciation yet retain the cultural heritage that these patterns hold so strongly since ages.